The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2478/boku-2019-0006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tillage depth of a cultivator on the incorporation of crop residues of winter barley in a chernozem soil

Abstract: Summary Although crop residues contribute to erosion control, the influence of the tillage depth (TD) on their incorporation has not been studied extensively. The main objective of this study was to determine the differences in the amount and distribution of incorporated crop residues and surface residue coverage if the TD of a cultivator is varied (0.10, 0.20, or 0.30 m). The experiment was carried out on a chernozem soil with winter barley residues in 2016 in Groß-Enzersdorf (Lower Austria). Individual soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…More residues are left with reduced tillage, although the amount depends on the particular method used. According to Mairhofer et al [52], after tilling with a cultivator, about 10-25% of residues remained on the surface, depending on depth of tillage. Tillage and sowing using the ST-OP system with 36 cm strip spacing, as carried out in our research, resulted in 62.7-74.7% of residues remaining on the field surface after wheat, and 75.7-82.0% after maize.…”
Section: Discussionmentioning
confidence: 99%
“…More residues are left with reduced tillage, although the amount depends on the particular method used. According to Mairhofer et al [52], after tilling with a cultivator, about 10-25% of residues remained on the surface, depending on depth of tillage. Tillage and sowing using the ST-OP system with 36 cm strip spacing, as carried out in our research, resulted in 62.7-74.7% of residues remaining on the field surface after wheat, and 75.7-82.0% after maize.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Staricka et al (1991) reported that mouldboard‐ploughing incorporated oat residue to a depth of 28 cm while chisel and disk ploughing incorporated the residues to 10 cm. Mairhofer et al (2019) demonstrated that spatial distribution of barley straw residue was unaffected by the increased tillage depth (10, 20 and 30 cm) in a chernozem soil, as more than 90% of the incorporated straw remained concentrated within the top 10 cm. These studies also reported highly clustered residue arrangement and patchy distribution with many voids without crop residue along with the tilled layer.…”
Section: Changes To Crop Residue Following Amelioration and Its Effec...mentioning
confidence: 99%